Potential Effects of Javanese Chili (Piper retrofractum Vahl.) Kombucha to Reduce Hyperglycemic and Maintain Spatial Memory: In Vitro and In Vivo Studies - Suyanti, Eri Dwi; Tsani, Salma Mutiara; Hanifah, Wafiq; Nastiti, Fithratun; Maatita, Marcellino; Farmawati, Arta (Universitas Ahmad Dahlan, 2025)
Type 2 Diabetes Mellitus (T2DM) and Alzheimer's Disease (AD) are diseases which incidence and prevalence increase with age. Diabetic patients have 50-75% higher risk of developing AD compared to patients without diabetes. This study aimed to determine the potential effect of Javanese chili kombucha to reduce hyperglycemia and to act as a neuroprotective in diabetes patients with a risk of AD complications through in vitro and in vivo studies. The experiment carried out was fermentation of Javanese chili kombucha for 3, 6, 9, 12 and 15 days. Organoleptic tests, pH measurements, total titratable acidity (TTA), antioxidant tests and α-amylase inhibition tests were conducted to determine the best duration for kombucha fermentation. Phytochemical screening and in vivo tests using 5 groups of rats included measurements of fasting blood glucose (FBG), malondialdehyde (MDA) assay and antidementia (T-maze). The 9th day fermentation preparation was the best preparation, with organoleptic test results of brown color, sour smell with a pH of 3.43 (safe), an antioxidant IC50 value of 10.5 (very strong), an α-amylase inhibition IC50 value of 117.14 (moderate) and TTA 1.44 (normal). Phytochemical screening results show that Javanese chili kombucha contains alkaloids, flavonoids, terpenoids/steroids, saponins, and phenolics. Based on in vivo tests, Javanese chili kombucha can reduce FBG levels and can maintain the spatial memory of experimental animals with a statistically significant T-maze duration time between groups. The MDA level test showed oxidative stress results that were not significantly different between groups.